Stabilization of positive switched delay systems with all modes unstable. (August 2018) - Liu, Zhi; Zhang, Xianfu; Lu, Xiaodong; Liu, Qingrong
Abstract: This paper studies the stabilization problem of positive switched delay systems (PSDSs) with all modes unstable. Multiple discretized co-positive Lyapunov–Krasovskii functionals are first introduced, by which a delay-dependent sufficient condition for global uniform asymptotic stability of continuous-time PSDSs is provided. It is shown that the state divergence generated by unstable subsystems can be validly compensated via dwell time switching. Moreover, the corresponding results are extended to the case of discrete-time PSDSs. Finally, a numerical example is given to illustrate the effectiveness of the theoretical results.